2004
DOI: 10.1080/03069880410001692238
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress, the blind men and the elephant

Abstract: Progress in understanding and developing effective responses to work-related stress has been elusive, patchy, and inconsistent. The reasons for this are reviewed, and the inadequacy of traditional stress management techniques and organisational interventions to tackle it are examined. Although necessary, clinical responses to distressed individuals and organisations in isolation can never deal effectively with the overall increasing levels of stress found. Neither can attempts to 'fit' individuals to cope with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
3
16
0
1
Order By: Relevance
“…Reference [24] identified that job satisfaction is an important predictor of overall well-being and employee intentions to quit. As a result, there is a relationship between job satisfaction and employee retention [25]. Reference [26] too concluded that job satisfaction is a positive outcome of WLB.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [24] identified that job satisfaction is an important predictor of overall well-being and employee intentions to quit. As a result, there is a relationship between job satisfaction and employee retention [25]. Reference [26] too concluded that job satisfaction is a positive outcome of WLB.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, many studies continue to use techniques which lack the sophistication to explore this complex and subjective process (see Dewe et al, 2010 for an overview of some notable exceptions). Overreliance on self-report questionnaires has drawn particular criticism, as they only capture a static moment in time, assuming any given stressful encounter is representative of an individual"s life situation (Lazarus, 1999;, resulting in "bits" of the process being taken out of their relational context (Bicknell & Liefooghe, 2006;Arthur, 2004;Aldwin, 2007;Lazarus, 1993;Dewe 1992). Exploring the complexity of appraisal and coping requires research designs which capture the process again and again, allowing us to understand stressful encounters in all aspects of the person"s life over time (Lazarus, 1999).…”
Section: Stress Appraisal and Coping Researchmentioning
confidence: 99%
“…Various individual and contextual factors will influence appraisal (Lazarus, 2003), and scholars argue that more innovative and creative research methods are required to capture the dynamic interaction of these factors (Dewe et al, 2010;Arthur, 2004;Briner et al, 2004;Dewe & Trenbeth, 2004;Dewe, 2003;Cooper et al, 2001;Lazarus 2000;O"Driscoll & Cooper, 1994;Somerfield & McCrae, 2000). Despite this, many studies continue to use techniques which lack the sophistication to explore this complex and subjective process (see Dewe et al, 2010 for an overview of some notable exceptions).…”
Section: Stress Appraisal and Coping Researchmentioning
confidence: 99%
“…These limitations also include low levels of relevance and applicability of these studies to counselling, coaching and to individuals themselves who seek to understand and cope with stressful situations in their lives. These authors believe that the above limitations stem from underestimating the complexity of personal factors associated with stress and an oversimplification of human nature (Arthur, 2004;Briner et al, 2004;Edwards & Harrison, 1993;Fletcher, 2002;Grimley, 2001;Guglielmi & Tatrow, 1998;Kyriacou, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…It has been argued that more integrated approaches to the study of stress and stress-management interventions are needed that take into account the self of those who suffer from stress within their social, economic and organisational contexts (Arthur, 2004;Dewe & Trenberth, 2004;Hopkins, 1997;Lazarus, 1990). For example, the transactional theory of Lazarus (1990Lazarus ( , 2000 suggests that stress is 'an ecological dysfunction' (Hopkins, 1997) brought about by an interplay of factors, including the individual.…”
Section: Introductionmentioning
confidence: 99%